Pengaruh Gaya Kepemimpinan Kepala Sekolah, Budaya Dan Pendidikan Terhadap Kinerja Guru Sekolah Menengah Pertama Negeri Di Kecamatan Bulang - Riduwan; Diana Riski Sapitri Siregar; Zahruddin (STIT Muhammadiyah Paciran, 2022)
Teacher performance can be interpreted as the result of work. achieved by a teacher in carrying out his duties in accordance with the responsibilities assigned to him. The purpose of the study was to determine the effect of the principal's leadership style, work environment, education, and training on the performance of SMP Negeri teachers in Bulang district simultaneously. This research uses quantitative research. The type of this research is descriptive research. The data analysis technique uses regression analysis with intervening path analysis. The population in this study were all teachers at SMP N in Bulang District as many as 135 people. The number of samples in this study were 119 respondents. Methods of data collection using the questionnaire method. The results of the Path Coefficient Models I and II research show that these results conclude that the Regression Model I, namely the variables X1 and X2 have a significant effect on Y. The contribution of X1 and X2 to Y is 40.7% while the remaining 59.3% is a contribution of other variables not included in the study. Meanwhile, for the value of e1 can be found using the formula e1 = (1-0.407) = 0.7701 and Regression Model II, it can be seen that the significance value of the three variables, namely X1 = 0.026, X2 = 0.043 and Y = 0.000 is smaller than 0.05. These results conclude that the Regression Model II, namely the variables X1, X2 and Y have a significant effect on Z.